Association of Systemic Inflammatory Response Syndrome with Bacteremia in Patients with Sepsis - Grozdanovski, Krsto; Milenkovikj, Zvonko; Demiri, Ilir; Spasovska, Katerina; Cvetanovska, Marija; Rangelov, Goran; Saveski, Velimir; Angelovska-grozdanovska Biljana (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2019)
The aim of this study was to evaluate the usability of systemic inflammatory response syndrome (SIRS) and commonly used biochemical parameters as predictors for positive blood culture in patients with sepsis. The study included 313 patients aged ≥18 years with severe sepsis and septic shock consecutively admitted in the Intensive Care Unit (ICU) of the University Clinic for Infectious Diseases in Skopje, Republic of North Macedonia. The study took place from January 1, 2011 to December 31, 2017. We recorded demographic variables, common laboratory tests, SIRS parameters, site of infection, comorbidities and Sequential Organ Failure Assessment (SOFA) score. Blood cultures were positive in 65 (20.8%) patients with sepsis. Gram-positive bacteria were isolated from 35 (53.8%) patients. From the evaluated variables in this study, only the presence of four SIRS parameters was associated with bacteremia, finding that will help to predict bacteremia and initiate early appropriate therapy in septic patients.
Keywords: bacteremia; sepsis; severe sepsis; septic shock